Clinically Meaningful Improvement Following Cervical Spine Surgery: 30% Reduction Versus Absolute Point-change MCID Values. Issue 11 (1st June 2021) - Khan, Inamullah; Pennings, Jacquelyn S.; Devin, Clinton J.; Asher, Anthony M.; Oleisky, Emily R.; Bydon, Mohamad; Asher, Anthony L.; Archer, Kristin R.
Abstract : Study Design: Retrospective analysis of prospectively collected registry data. Objective: The aim of this study was to compare the performance of 30% reduction to established absolute point-change values for measures of disability and pain in patients undergoing elective cervical spine surgery. Summary of Background Data: Recent studies recommend using a proportional change from baseline instead of an absolute point-change value to define minimum clinically important difference (MCID). Methods: Analyses included 13, 179 patients who underwent cervical spine surgery for degenerative disease between April 2013 and February 2018. Participants completed a baseline and 12-month follow-up assessment that included questionnaires to assess disability (Neck Disability Index [NDI]), neck and arm pain (Numeric Rating Scale [NRS-NP/AP], and satisfaction [NASS scale]). Participants were classified as met or not met 30% reduction from baseline in each of the respective measures. The 30% reduction in scores at 12 months was compared to a wide range of established absolute point-change MCID values using receiver-operating characteristic curves, area under the receiver-operating characteristic curve (AUROC), and logistic regression analyses. These analyses were conducted for the entire patient cohort, as well as for subgroups based on baseline severity and surgical approach. Results: Thirty percent reduction in NDI and NRS-NP/AP scores predicted satisfaction with more accuracy than absolute point-change values for the total population and ACDF and posterior fusion procedures ( P  < 0.05). The largest AUROC differences, in favor of 30% reduction, were found for the lowest disability (ODI 0–20%: 16.8%) and bed-bound disability (ODI 81%–100%: 16.6%) categories. For pain, there was a 1.9% to 11% and 1.6% to 9.6% AUROC difference for no/mild neck and arm pain (NRS 0–4), respectively, in favor of a 30% reduction threshold. Conclusion: A 30% reduction from baseline is a valid method for determining MCID in disability and pain for patients undergoing cervical spine surgery. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the text